Exploration of candidate serum biomarkers potentially related to the chronic pain condition in Medication–overuse headache - Pellesi, Lanfranco (BMC Neurol, 2019)
BACKGROUND: Medication Overuse Headache (MOH) is a prevalent and disabling disorder resulting from the overuse of analgesic drugs, triptans or other acute headache medications. In previous proteomic studies, several proteins have been found at high concentrations in the urine of MOH patients and in the serum of rats with neuropathic pain. The aim of this study was to compare the serum levels of lipocalin-type Prostaglandin D2 synthase (L-PGDS), Vitamin D-binding protein (VDBP), apolipoprotein E (APOE) and apolipoprotein A1 (APOA1) in MOH patients and healthy individuals, further exploring their relationship with cutaneous pain thresholds (CPTs) in the territories innervated by the trigeminal nerve. METHODS: Sixty-nine MOH patients and 42 age- and sex-matched healthy volunteers were enrolled in the study. Von Frey-like filaments were applied to the skin territories innervated by the trigeminal nerve, to determine the CPTs. L-PGDS, VDBP, APOE and APOA1 were quantified in the serum by Enzyme-linked Immunosorbent Assay (ELISA). Clinical and laboratory data were collected. Comparisons between MOH patients and healthy individuals were performed using independent t test or χ(2) test. To correlate serum proteins with CPTs, Pearson correlation coefficient or Spearman’s rank correlation coefficient were used. RESULTS: CPTs were lower among MOH patients. L-PGDS, VDBP and APOE had significantly different serum concentrations between groups (p < 0.01), but no correlation was found with CPTs. APOA1 serum concentrations did not differ between patients and healthy individuals. CONCLUSIONS: L-PGDS, VDBP and APOE had abnormal serum levels in MOH patients, confirming their alteration in some conditions of chronic headache and neuropathic pain. However, they had no relationship with CPTs. The in-depth study of serum proteins represents a promising approach for a better understanding of MOH, as well as the detection of candidate biomarkers for chronic headache or the risks associated with overuse medications.